Undilatable Stent Neoatherosclerosis Treated with Ad Hoc Rotational Atherectomy - Michael Koutouzis; Maria Agelaki; Christos Maniotis; Ioannis Tsiafoutis; Vasileios Patris; Mihalis Argyriou (Case Reports in Cardiology)
A middle age woman with known ischemic heart disease and old stents in proximal left anterior descending coronary artery (LAD) was admitted to Coronary Care Unit with acute coronary syndrome. The coronary angiography showed one vessel disease with significant restenosis within the previously implanted stents. The lesion was tough and remained undilatable despite high pressure balloon inflation. Eventually, the balloon ruptured creating a massive dissection of the LAD beginning immediately after the distal part of the undilatable lesion. We proceeded with a challenging ad hoc rotational atherectomy of the lesion and finally stenting of the lesion. In-stent restenosis many years after stent implantation is considered to be mainly due to neoatheromatosis compared to intimal hyperplasia, making lesion treatment more difficult and unpredictable.